Frequency Property Analysis of Dynamic Component of Heat-Transfer Agent Behaviour in Main Pipeline - N. A. Avtushenko; G. S. Lenevsky (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
In order to assess behaviour of a heat-transfer agent in the main hot water supply methodology for calculation of an object as a system with distributed parameters on the basis of Navie- Stokes equation and medium continuity equation has been developed in the paper. Calculation is carried out with due account of frequency properties of transfer functions of the heat-transfer agent.